Sistema de comercialización y su incidencia en la rentabilidad de la empresa la Ganga de la Ciudad de Quevedo periodo 2013-2014, plan de marketing. - Pilligua Vera, Carlos Alberto (2016)
Ganga stores started operations in 1983, opening its first store in the area of "The Bay" in the city of Guayaquil, since its inception, specializing in the marketing and sale of appliances of the best global brand, offering far and competitive advantage their products. With effort and tenacity, the company has achieved leadership in a difficult and competitive market. The overall objective planted in the investigation was assessing the impact of the marketing system in the store's profitability Ganga during 2013-2014. To achieve this objective information was collected through surveys conducted for the citizens of Canton and store administered interview. The Ganga determined that warehouse does not have a marketing system that meets the needs of customers making many of them look for places where they meet their needs significantly affect the profitability of the company. This research aims to recover these customers by implementing a marketing plan which will allow the company to establish significant strategies in place to capture and recovery of dissatisfied customers and thus better profitability.